Effect of wedge disclination dipole on dislocation emission from a surface crack tip in nanocrystalline materials. (February 2016) - Wang, Z.P.; Feng, H.; Liu, F.; Fang, Q.H.; Liu, Y.W.; Wen, P.H.
Highlights: Study the interaction between wedge disclination dipole and surface crack tip. Dislocations emit from a surface crack tip in nanocrystalline materials. Disclination strength and emission angle for critical SIFs are discussed. Disclination dipole induces the shielding effect at the crack tip. Larger disclination strength can promote crack propagation and decrease toughness. Abstract: The interaction between a wedge disclination dipole and a linear crack of the surface in nanocrystalline materials is investigated. Utilizing the conformal mapping technique and the Muskhelishvili complex variable method, the explicit closed-form solutions are derived for complex potentials and stress fields. The critical stress intensity factors (SIFs) for the first dislocation emission from the crick tip are also calculated. The effects of the relative parameters on the normalized critical SIFs, such as the disclination strength, the edge dislocation emission angle, the dipole size, the distance between the crack tip and the center of the disclination dipole, the direction angle of the disclination dipole and the crack length, are discussed in detail as well. The results reveal that the shielding effect produced by disclination dipole increases with the increasing disclination strength, which means it can prevent the dislocation emission from the crack tip to decrease material toughness.